Economic Voting and the Clarity of Available Alternatives - DAVIS, Brent (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
The vast economic voting literature is based on two simple foundations: economics matters to voters when forming their vote decision; and, they are able to clearly identify whom to hold politically accountable for economic policy settings and outcomes (that is, ‘clarity of responsibility’). This article argues this two-pillar approach is incomplete, and needs to be strengthened with a third pillar: voters also need ‘clarity of available alternatives’. That is, voters also need to have a clear sense of the availability of credible alternatives, likely to be able to deliver superior outcomes, to the incumbent if they are to switch their vote. In short, they are less likely to vote out the incumbent if the available alternative is less credible.